Establishment of Seed Production Area of Tectona grandis Linn. f. in Gujarat - Mishra, D K; Tewari, V P; Tripathi, S P; Bohra, N K; Emmanuel, C J S K (Annals of Arid Zone, 2017)
Teak is a slow growing species and any tree improvement program will take 15-40 years before the timber from the first rotation of improved planting stock is harvested. Ten to fifteen years may pass from the initiation of an improvement program before improved seed is available. Developing seed production areas (SPAs) is one of the first steps in tree improvement program that can be used to obtain genetically improved seed for immediate planting but it is usually for the short term in nature. Though seeds obtained from this method do not yield large volume of genetic gain, it sometimes greatly improves tree quality. After survey of nearly 940 ha plantations of Tectona grandis at 15 locations in Gujarat, 85 ha at six sites were converted into seed production areas (SPAs) after inter-comparing with various other seed stands. After culling of inferior trees from these six stands, the average height, clear bole, girth at breast height, diameter at breast height and volume were shifted towards the higher side in all the stands. Seeds collected from these seed production area performed better in seed attributes than un-culled stands